2021
DOI: 10.3389/fphar.2020.606689
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Fecal Microbiome and Serum Metabolomics Analysis Reveals Abnormal Changes in Rats with Immunoglobulin A Nephropathy and the Intervention Effect of Zhen Wu Tang

Abstract: Immunoglobulin A nephropathy (IgAN), an autoimmune renal disease with complicated pathogenesis, is one of the principal reasons for end-stage renal disease in the clinic. Evidence has linked apparent alterations in the components of the microbiome and metabolome to renal disease in rats. However, thus far, there is insufficient evidence that supports the potential relationship between gut microbiome, circulating metabolites, and IgAN. This study was designed to probe the effects of IgAN on intestinal microecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The combination of chemical drugs and Yinxingdamo injection and chemical drugs and Danhong injection had the potential to be the best Chinese herbal injections relative to total clinical effectiveness, serum albumin, and 24-h urinary protein excretion. Moreover, Li et al (2020b ) and Li et al (2020c ) demonstrated that Zhen-Wu-Tang could ameliorate immunoglobulin A nephropathy in rats.…”
Section: Treatment Of Membranous Nephropathymentioning
confidence: 98%
“…The combination of chemical drugs and Yinxingdamo injection and chemical drugs and Danhong injection had the potential to be the best Chinese herbal injections relative to total clinical effectiveness, serum albumin, and 24-h urinary protein excretion. Moreover, Li et al (2020b ) and Li et al (2020c ) demonstrated that Zhen-Wu-Tang could ameliorate immunoglobulin A nephropathy in rats.…”
Section: Treatment Of Membranous Nephropathymentioning
confidence: 98%
“…These biomarkers of metabolites were mainly involved in lipid metabolism, signal transduction, carbohydrate metabolism, amino acid metabolism, and biosynthesis of other secondary metabolites ( 29 ). They may be a core metabolite of IgAN and may be an important mediator between intestinal and blood circulation ( 46 ).…”
Section: Roles Of Metabolites From Microbiota In Iganmentioning
confidence: 99%
“…Feeding of Zhen Wu Tang to IgAN model rats significantly changed the gut microbiota with increased the relative abundance of microbial species at the family level, including Peptostreptococcaceae and Family_XIII while suppressing the abundances of Cyanobacteria and Proteobacteria . Moreover, the model group had higher abundance of Lachnospiraceae, Lactobacillaceae, Erysipelotrichaceae , and Bacteroidaceae relative to the normal group; ZWT intervention reduced these levels ( 46 ). Zhen Wu Tang can improve the microecological imbalance and reduce kidney damage in IgAN rats ( 46 ).…”
Section: Microbiota-targeted Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a close interconnection has been proposed between the gut and kidney, which is known as the gut–kidney axis ( Khoury et al, 2017 ; Chen et al, 2019 ). The association between fecal microbiome and serum metabolomics in IgA nephropathy rats and the intervention effect of ZWD have been reported ( Li et al, 2021 ). However, whether ZWD attenuates renal fibrosis through modifying the gut microbiota remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%